Patterning types of aggressive behaviour of primary school children with speech disorders - Bielova, Olena (Special Education, 2020)
In order to understand the relationship between speech disorders and aggressive behaviour, the dependence of aggressive behaviour in young school-age children on their speech disorders was studied experimentally. The study had 286 children (6 to 10 years old), 57% of them with typical psychophysical development and 43% with speech disorders in Ukrainian schools. According to the results of the summary of the scientific methods, there have been discoveries of three types of aggression and six subtypes of aggression and also their features: the self-regulating type of aggression incorporates the controlled and the competitive subtypes; covert type – defensive and depressive; behavioural type – demonstrative and physical. The findings indicate that the more complex the speech disorder is, the greater the manifestation of depressive, demonstrative and physical aggression is. The more complex the state of aggression is, the harder it is to realize it. A child cannot always overcome such states on his/her own; therefore, he/she needs co-education, adult assistance.